2016
DOI: 10.1007/s40261-016-0471-2
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Outcomes in Fingolimod-Treated Patients with Multiple Sclerosis in the Czech Republic: Results from the 12-Month GOLEMS Study

Abstract: Background and ObjectiveOnce-daily oral fingolimod is approved in the EU as escalation treatment for adult patients with highly active relapsing multiple sclerosis (MS). The efficacy and safety profiles of fingolimod have been well established in a large clinical development programme and several papers reflecting the experience with fingolimod in real-world settings have been published to date. The GOLEMS study was designed to evaluate the efficacy, safety and tolerability of fingolimod and the impact of fing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 23 publications
5
18
0
Order By: Relevance
“…In our population, and similar to other studies [11,15,18,19,30], fingolimod has shown to have a good safety profile. The proportion of patients discontinuing treatment was mostly related to disease activity (5.5%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our population, and similar to other studies [11,15,18,19,30], fingolimod has shown to have a good safety profile. The proportion of patients discontinuing treatment was mostly related to disease activity (5.5%).…”
Section: Discussionsupporting
confidence: 91%
“…These attrition rates are similar to the ones found in the present study (9.8%), which are also similar to the ones reported by the real-word study with fingolimod from UK (approximately 8%) [13]. In other two real-world studies, one conducted in the Czech Republic, the GOLEMS study, 11.3% of patients discontinued fingolimod at N, number of patients; %, percentage of total; ULN, upper limit of normal a Three opportunistic infections, one hepatic enzymes > 3 × ULN and one disease activity could not be assigned to a specific year given the dates are lacking or before 12 months [19] and another one conducted in Spain, the MS NEXT, 3.9% of patients permanently discontinued fingolimod during the first year of treatment [20]. Overall, the proportion of relapse-free patients significantly increased from 78.9 to 90.5% from the first to the third year after switching to fingolimod therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The overall pattern of AEs or SAEs reported with long-term fingolimod treatment was similar to those reported in the feeder studies, 812 and from real-world studies. 1319 In line with those previous studies, the most commonly reported AEs were headache, lymphopenia, and influenza, all of which showed a clear decreasing trend from year 1 to year 11 in LONGTERMS. In addition to selective drop out in the feeder studies, such a decrease in reported AEs could be due to reduced reporting by the investigators or patients who had adapted to recurring similar AEs.…”
Section: Discussionsupporting
confidence: 89%
“…Fingolimod (FTY720, Gilenya®), a sphingosine 1-phosphate receptor (S1PR) modulator, was the first oral DMT approved for the treatment of relapsing MS (RMS), 57 after efficacy and safety were demonstrated in pivotal phase III clinical trials against placebo (FREEDOMS, 8 FREEDOMS II 9 ) and interferon (IFN) beta-1a (TRANSFORMS). 10 First reports from extension studies 11,12 and from the use of fingolimod in real-world settings across different geographical regions 1319 were consistent with the results of the pivotal studies. However, as for other DMTs, longer-term data on safety and efficacy of fingolimod are needed to optimize treatment strategies for MS disease management in routine clinical practice.…”
Section: Introductionsupporting
confidence: 58%
“… 44 Reports from observational studies with an observational period of 12 months give AE incidence rates of 35% to 60%. 45 , 46 Noteworthy is that no participant reported any cardiovascular adverse event during the six-month study period. The proportion of relapse-free PwMS during the study period was about 90% in both groups.…”
Section: Discussionmentioning
confidence: 99%